Perception of the Organizational Climate and Organizational Citizenship Behavior of Department of Human Resources and Compliance Thai Airways International Public Co,.Ltd - ศรีศิลารักษ์ รพีพัฒน์; พสุนนท์ ประสพชัย (Business Administration and Management Journal Review, 2016)
The objectives of this research are to study the perception of the organizational climate of the Human Resources and Compliance; to study the organizational citizenship behavior of the Human Resources and Compliance; to compare the perception of the organizational climate by individuals; to compare the perception of the organizational citizenship behavior by individuals; and to study the influence of the organizational climate perception on the organizational citizenship behavior of the Human Resources and Compliance. Samples used in this study were Human Resources and Compliance. Statistical methods used for the analysis were percentage, mean, standard deviation, analysis of variance, ANOVA and Simple Regression Analysis. The results of this study indicate that the government employees of the Human Resources and Compliance, in general, have a high degree of perception of the organizational climate. When analyzing for each subcategory, the results reveal that the perception of autonomous climate is at high level, followed by the organizational structure, organizational support, the relationship within the organization, and change management, respectively. The results also show that, generally, the government employees of the Human Resources and Compliance have a medium degree of organizational citizenship behavior. If viewed by category detail, the study indicates that compliance and altruism are at high level, followed by sportsmanship, courtesy, and conscientiousness, respectively. The relationship between the perception of the organizational climate and organizational citizenship behavior was positive and rather significant and benefits to the organization in understanding the condition of the organization and development organizations such as human resource development, organizational structure etc.